From translation to imitation / Od tłumaczenia do naśladowania (tłum. Wojciech Tokarz) - Jackson, Richard (Przekłady Literatur Słowiańskich, 2015)
From translation to imitation Translation is not only an important way to learn the art of poetry, but also provides a way to understand other cultures. However, it is mostly misunderstood: some would desire a literal translation even if the spirit of the text is lost, others a loose version even if the meaning is lost. Everything we write is already a translation in that is made of words as opposed to the original experience, and every translation is then necessarily an interpretation. Literary translation involves trying to recreate the experience of the original, and this can be done in ways ranging from actual translation to imitation. Key words: Translation, Imitation, poetry, paraphrase, adaptation